2016
DOI: 10.1002/spe.2430
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive object‐oriented approach to big surveillance data compression for social security applications in smart cities

Abstract: Surveillance has become a fairly common practice with the global boom in "smart cities". How to efficiently store and manage the vast quantities of surveillance data is a persistent challenge in terms of analyzing social security problems. Developing data compression technology under the analytic requirements of surveillance data is the key to solving the storage problem. Criminal investigation demands the quality preservation of sensitive objects, typically pedestrians, human faces, vehicles, and license plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Some studies criticised the existing work and proposed new solutions (Gope et al 2018;Xie and Hwang 2019;Zang et al 2017). For example, Xie and Hwang (2019) showed that the scheme proposed by Xiao et al (2017) lacks two-factor security, and suffers from an impersonation attack. To mitigate these problems, an improved roaming authentication protocol with two-factor security was proposed, secured by using an applied pi calculus-based formal validation tool ProVerif demonstrating enhanced efficiency in comparison with some related schemes.…”
Section: Framework Models Algorithms and Protocols To Improve Security And Privacymentioning
confidence: 99%
“…Some studies criticised the existing work and proposed new solutions (Gope et al 2018;Xie and Hwang 2019;Zang et al 2017). For example, Xie and Hwang (2019) showed that the scheme proposed by Xiao et al (2017) lacks two-factor security, and suffers from an impersonation attack. To mitigate these problems, an improved roaming authentication protocol with two-factor security was proposed, secured by using an applied pi calculus-based formal validation tool ProVerif demonstrating enhanced efficiency in comparison with some related schemes.…”
Section: Framework Models Algorithms and Protocols To Improve Security And Privacymentioning
confidence: 99%
“…Future studies will be given to further exploring the relationship between content and style and their representations to further improve inpainting performance. We will also further look into the no reference quality assessment (Fang et al 2018) for inpainting and the generalization to applications, such as context-based coding (Xiao et al 2016) and disocclusion-based analysis (Xiao et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For example, loudspeaker triplet selection can be used during the process of the multichannel simplification, the technique for loudspeakers triplet selection can be used in the quantization of spatial parameters, and the multichannel down‐mixing method can be modified by the proposed method to improve the performance of 3D audio coding and decoding. Furthermore, if the surveillance cameras can capture audio signals, phantom source localization method can also help locate the object of interest in the surveillance video …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, if the surveillance cameras can capture audio signals, phantom source localization method can also help locate the object of interest in the surveillance video. 30,31,32 Another popular research topic in addition to the loudspeaker array playback is binaural acoustic signal reconstruction. After accurately recording the binaural acoustic signals of the original sound source and playing them back by headphone, the listener perceives the location of the reconstructed sound source as identical to the original sound source.…”
Section: Discussionmentioning
confidence: 99%